Nutrition Support in Burn Patients - Cem Aydoğan; Yahya Ekici (Galenos Yayinevi, 2012)
Severe burn trauma causes serious metabolic derangements. Increased metabolic rate which is apart of a pathophysiologic characteristic of burn trauma results in protein-energy malnutrition. This situation causes impaired wound healing, muscle and fat tissue's breakdown, growth retardation in children and infections. Nutrition support is vital in the treatment strategies of burn victims to prevent high mortal and disabling complications in this devastating trauma. Our aim in this study is to review management of nutrition in burn victims. (Journal of the Turkish Society Intensive Care 2012; 10: 74-83)